2019
DOI: 10.1007/s11904-019-00446-5
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Rising STIs in the Era of PrEP and Treatment as Prevention

Abstract: Purpose of Review:To review the epidemiology of sexually transmitted infections (STIs) among men who have sex with men (MSM) and suggest control measures.Recent findings: Despite declines in new HIV diagnosis, bacterial STIs among MSM have dramatically risen since the late 1990s. This increase occurred concurrent with introduction of effective antiretroviral therapy, the advent of electronic mechanisms for meeting sex partners and population-level changes in sexual behavior, including decreased condom use. HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 100 publications
(90 reference statements)
0
42
1
1
Order By: Relevance
“…Although the reasons for this are not well established, they have been correlated with increases in condomless anal intercourse and numbers of sexual partners 6 , 8 , 21 and associated with HIV biomedical strategies, such as treatment used as prevention. 22 , 23 The main difference between our studies and others is that we found that the STI test positivity rate after commencing PrEP stabilized. These findings are consistent with those of an international meta-analysis 24 of PrEP use that found no change in the proportion of MSM reporting condomless sex from baseline to follow-up while taking PrEP, which suggests that groups of study participants use condoms inconsistently and regardless of PrEP use.…”
Section: Discussioncontrasting
confidence: 86%
“…Although the reasons for this are not well established, they have been correlated with increases in condomless anal intercourse and numbers of sexual partners 6 , 8 , 21 and associated with HIV biomedical strategies, such as treatment used as prevention. 22 , 23 The main difference between our studies and others is that we found that the STI test positivity rate after commencing PrEP stabilized. These findings are consistent with those of an international meta-analysis 24 of PrEP use that found no change in the proportion of MSM reporting condomless sex from baseline to follow-up while taking PrEP, which suggests that groups of study participants use condoms inconsistently and regardless of PrEP use.…”
Section: Discussioncontrasting
confidence: 86%
“…may facilitate an increase in risky sexual practices to the order of up to 21% [49][50][51][52][53][54]. A Latin Hypercube Sampling (LHS) analysis over 6,000 possible parameter sets was utilised, the values of which are described in Table 5.…”
Section: Plos Onementioning
confidence: 99%
“…A range of studies reported that availability of HIV control interventions ART and PrEP can facilitate behavioural disinhibition where risk behaviours are increased in a population [49][50][51][52][53][54].…”
Section: Condom Usagementioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis suggested that PrEP use was associated with a 24% increase in the prevalence of STI and a 59% increase in the risk of rectal STI among users [ 15 ]. Although STI among MSM are seldom life-threatening, they are morbid and associated with increasing medical cost, and likely to increase risk of HIV transmission [ 20 ]. Therefore, the PrEP clinical practice guideline issued by the United States Centers for Disease Control and Prevention (CDC) highlights the importance of regular STI testing for PrEP users [ 21 ].…”
Section: Introductionmentioning
confidence: 99%